Гідродинамічні характеристики нестабілізованої двошарової течії узагальнених ньютонівських рідин - Желяк, В.; Кончевич, Я.; Регуш, А. (Видавництво Національного університету “Львівська політехніка”, 2005)
In activity it is ground usages of an allocation procedure the equations for the description of two-layer non-stabilized flow are obtained. The outcomes of a numerical modeling circumscribing geometrical, kinematic and dynamic parameters of a two-layer flow are submitted.
Keywords: 532.516